Cytopathological review of cervical pathology: Impact for women and follow‐up results. (21st February 2020) - Scheck, Simon M.; Lepine, Sam J.; Yu, Helen; Robb, Olivia; Fitzgerald, Peter; Clentworth, Howard; Maharaj, Dushyant; Tully, Linda; Tristram, Amanda
Abstract : Background: Cervical screening programs have had an important effect on the reduction of cervical cancer rates. Comprehensive programs require access to pathological review to improve the sensitivity of screening cytology and the specificity of diagnostic histology. Aims: To determine the number of cases where cervical cytology or histology was amended at cytopathological review; whether amendments were 'upgrades' or 'downgrades', and how amendments aligned with follow‐up results for these patients. Materials and Methods: A retrospective cohort study was performed of all patients reviewed from January 2016 to December 2017 ( n = 287 cases, from 254 patients) at colposcopy multidisciplinary meetings at Wellington Hospital, a tertiary referral hospital. Where amendments to cytology or histology were made, follow‐up results were retrieved where available (85.7% and 84.2% respectively). Results: Cytology or histology was amended in 24.7% of cases. Smear cytology was amended in 16.7%. Where cytology was upgraded ( n = 9), 44% had subsequent results of equal or higher grade including one case of adenocarcinoma. Where cytology was downgraded ( n = 19), 93.8% (81.9–100%) had follow‐up studies showing equal or lower results. Cervical biopsy histology was amended in 12.2% of cases (upgraded n = 19, downgraded n = 6). Large loop excision of the transformation zone or cone biopsy histology was amended in three cases (7.9%). Conclusions: Cytopathological review appears to improve the specificity of the comprehensive cervical screening program, leading to a reduction in unnecessary treatment. Additionally, a small number of cases of malignant or premalignant disease were detected.